2013
DOI: 10.1063/1.4789705
|View full text |Cite
|
Sign up to set email alerts
|

Do perceptually salient elements in physics problems influence students' eye movements and answer choices?

Abstract: Several reasons have been proposed to explain students' incorrect answers to conceptual physics problems. Heckler [3] proposed with a perceptual basis: plausible and salient "eye catching" features in a problem capture students' attention. Once students attend to these perceptually salient features, less salient albeit thematically relevant features are not considered and students answer the problem incorrectly based on the salient features. To test this hypothesis we recorded eye movements of introductory phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…Nevertheless, there is a critically important difference between the results of our studies and those of Grant and Spivey (2003) and Thomas and Lleras (2007 , 2009 ), who proposed the provocative idea that simply having the viewer’s low-level attentional movements embody a problem’s solution is sufficient to facilitate finding the correct solution. Specifically, our research, including both the current and previous studies ( Madsen et al, 2013a , b ) has shown that while attending to relevant information in a problem is a necessary condition for correctly solving the problem, it is generally not sufficient to correctly solving it. The current study has specifically shown that cues, which both draw attention to solution-relevant information, and facilitate organizing and integrating it, facilitate both immediate problem solving and generalization of that ability to new problems.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Nevertheless, there is a critically important difference between the results of our studies and those of Grant and Spivey (2003) and Thomas and Lleras (2007 , 2009 ), who proposed the provocative idea that simply having the viewer’s low-level attentional movements embody a problem’s solution is sufficient to facilitate finding the correct solution. Specifically, our research, including both the current and previous studies ( Madsen et al, 2013a , b ) has shown that while attending to relevant information in a problem is a necessary condition for correctly solving the problem, it is generally not sufficient to correctly solving it. The current study has specifically shown that cues, which both draw attention to solution-relevant information, and facilitate organizing and integrating it, facilitate both immediate problem solving and generalization of that ability to new problems.…”
Section: Discussionmentioning
confidence: 70%
“…Prior research on eye movements and problem solving has shown that overt attention can illuminate the cognitive processes involved in problem solving ( Epelboim and Suppes, 2001 ; Knoblich et al, 2001 , 2005 ; Grant and Spivey, 2003 ; Jones, 2003 ; Thomas and Lleras, 2007 , 2009 ; Bilalić et al, 2008 ; Eivazi and Bednarik, 2010 , 2011 ; Madsen et al, 2012 , 2013a , b ; Lin and Lin, 2014 ; Susac et al, 2014 ). However, we are particularly interested in two directions of causal relationships between overt attentional selection and the higher-level cognitive processes involved in problem solving: (1) the causal relationship starting from higher-level cognitive processes involved in problem solving and ending with attentional selection; and (2) the reverse causal relationship starting from attentional selection and ending with the higher-level cognitive processes involved in problem solving.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial tasks used in this study were from the Force Concept Inventory (FCI) validated by Hestenes and collaborators [31]. Near and far transfer tasks used in this study had been validated in previous studies [32][33][34][35].…”
Section: B Proceduresmentioning
confidence: 99%